2007
DOI: 10.12681/bgsg.16733
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical and Chemical Composition of CFB Fly Ash Derived From Co-Combustion of Xylite and Biomass

Abstract: The chemical and mineralogical composition of fly ash samples collected from different parts of two Circulating Fluidised Bed (CFB) facilities has been investigated. The fuels used, were Greek xylite/suhbituminous coal (from the Fiorina basin), Polish coal (from the Catowice region -Poland) and wood chips (Swedish conifer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Research has shown that biochar can adsorb organic substrates, phosphate, nitrate, nitrite, ammonium, metals and carbon dioxide (Bagreev et al, 2001). According to Koukouzas et al (2007) DeLuca et al, 2006). Le Leuch and Bandosz (2007) showed that the sorption of ammonium by biochar immobilizes the ammonium concentration in soil thus reducing the volatilization of ammonium to ammonia under alkaline conditions and during temperature changes within the soil.…”
Section: Nutrient Retentionmentioning
confidence: 99%
“…Research has shown that biochar can adsorb organic substrates, phosphate, nitrate, nitrite, ammonium, metals and carbon dioxide (Bagreev et al, 2001). According to Koukouzas et al (2007) DeLuca et al, 2006). Le Leuch and Bandosz (2007) showed that the sorption of ammonium by biochar immobilizes the ammonium concentration in soil thus reducing the volatilization of ammonium to ammonia under alkaline conditions and during temperature changes within the soil.…”
Section: Nutrient Retentionmentioning
confidence: 99%
“…All samples showed the presence of quartz. According to N. Koukouzas et al (2007), the ash from bituminous coal contains high amounts of silicon dioxide. Besides that, all samples show the present of hematite (Fe 2 O 3 ), accompanied by anhydrite, due to the reactions between pyrite sulfur and calcite [7].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the vast majority of NW Greece fly ashes are classified as Class-C. Fly ashes from the Almyros basin are poor in SiO 2 , Al 2 O 3 and Fe 2 O 3 and rich in CaO contents, whereas their plots lie closer or within the Class-C field (Figure 2b; [28]).…”
Section: Classification and Geochemical Features Of Fly Ashesmentioning
confidence: 99%